2016
DOI: 10.4172/2472-0429.1000117
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancer Awareness and Attitude among Adult, Al-Dammam, Saudi Arabia

Abstract: Background: The aim of this study was to determine the level of knowledge about colorectal cancer (CRC) in adult healthy individuals in Eastern Province of Saudi Arabia. The main point of the current study was the need to increase the level of awareness of CRC to establish a link between the public, health centers and educational institutions to spread the awareness of CRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
4
1
Order By: Relevance
“…In a previous Saudi study [31], it was reported that most of the participants believed that screening of colorectal cancer should be performed before the onset of symptoms, which was in contrast with our findings. There were 42.9% of participants from a study in Riyadh reported that screening of colon cancer should begin at the onset of symptoms [32].…”
Section: Attitude Of Participants About Early Detection Of the Invest...contrasting
confidence: 99%
See 1 more Smart Citation
“…In a previous Saudi study [31], it was reported that most of the participants believed that screening of colorectal cancer should be performed before the onset of symptoms, which was in contrast with our findings. There were 42.9% of participants from a study in Riyadh reported that screening of colon cancer should begin at the onset of symptoms [32].…”
Section: Attitude Of Participants About Early Detection Of the Invest...contrasting
confidence: 99%
“…A study conducted on Saudi Adults in Al-Dammam demonstrated that less than 30% reported that red meat is a risk factor for colorectal cancer, 18% reported diabetes, and 53% reported family history as risk factors [31].…”
Section: Attitude Of Participants About Early Detection Of the Invest...mentioning
confidence: 99%
“…Additionally, food and smoking were mentioned as risk factors by approximately 61%, while 45% mentioned IBD [ 6 ]. In the western region of Saudi Arabia, a little over two-thirds of respondents reported a low-fiber diet and smoking as risk factors for CRC in a study by Alnuwaysir et al [ 22 ]. Alsayed et al in Al-Madinah Al-Monawarrah, Saudi Arabia, indicated that 35.5%, 62.2%, and 57.1% of respondents reported that family history, smoking, and colon polyp are risk factors for CRC, respectively [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further studies assessing the knowledge of teachers in Saudi Arabia regarding colorectal cancer found that 39% of male teachers and 42% of female teachers were unaware of the screening methods involved in colorectal cancer [31]. A study assessing the knowledge of CRC screening in 402 participants concluded that patients of higher age and higher educational status were more knowledgeable about CRC and its screening methods and believed that screening before the disease reaches an advanced stage is beneficial [32].…”
Section: Patient-related Factors For Screening Compliancementioning
confidence: 99%
“…The overburdened primary healthcare system is one of the challenges that implementation of CRC screening faces because an efficient and active primary care system is essential for successful establishment of screening tests [37]. Studies show that physician recommendations to obtain screening is the major facilitator for patients to undergo screening for CRC, while at the same time, not receiving a recommendation to undergo screening is its biggest obstacle [17,[28][29][30][31][32][33][34][35][36][37][38].…”
Section: Physician-related Factors For Screening Recommendationsmentioning
confidence: 99%